Gamma ray interaction of germanoborate glasses for radiation shielding applications - Chanthima, Natthakridta; Yonphan, Supakit; Mutuwong, Chalermpon; Chaiphaksa, Wuttichai; Kaewkhao, Jakrapong (Journal of Associated Medical Sciences, 2025)
Background: Ionizing radiation is essential in medical imaging and therapy, but it also poses health risks to medical staff and patients. Traditional shielding materials like lead are effective but toxic, while concrete lacks transparency. Therefore, glass systems incorporating high-Z oxides offer a promising alternative by combining optical clarity with enhanced radiation shielding performance. Objectives: This study aims to develop and investigate germanoborate glasses doped with Gd2O3, with a particular focus on their photon attenuation properties. The findings are intended to development of transparent, lead-free radiation shielding materials suitable for medical and industrial applications. Materials and methods: The Gd2O3 added germanoborate glasses in the system (60-x)B2O3-GeO2-x Gd2O3 (with x=10, 20, 30 and 40 mol%) were synthesized via melting at 1400 oC followed by melt quenching method. The densities were measured by Archimedes’ method. The mass attenuation coefficients (μm), the effective atomic number (Zeff), the effective electron density (Neff), and half-value layers (HVL) were computed using the WinXCom program (NIST XCOM Database) to assess shielding properties. PHITS Monte Carlo simulations were employed to calculate the effective dose rate. Results: The addition of Gd2O3 increased the glass density from 3.7546 gm/cm³ to 5.4604 gm/cm3. Replacing B2O3 with Gd2O3 enhanced the mass attenuation coefficients (μm), effective atomic number (Zeff) and effective electron density (Neff). HVL values decreased, Pb equivalent values increased, and the effective dose was reduced. Conclusion: The incorporation of Gd2O3 into germanoborate glasses significantly enhances their gamma-ray attenuation capabilities, confirming their effectiveness as lead-free shielding materials. The developed glasses exhibit optimized radiation protection properties, highlighting their potential for transparent shielding applications in medical, industrial, and nuclear fields. and infliximab exert protective effects on liver function in acetic acid induced UC model. These findings suggest potential benefits of these therapies in mitigating liver damage associated with UC, highlighting the importance of considering liver health in UC management.